A competitividade do Brasil e da China no mercado Norte-Americano: 2000-2008 - Marina Filgueiras; Honorio Kume (Instituto de Pesquisa Econômica Aplicada (IPEA), 2010)
– This study analyses how the set of products Brazil exported to the United States was similar with that of China between 2000 and 2008 and also compares the quality and variety of their exports. Using product-level import data from United States, this study estimates the export similarity, quality and variety indexes and produces three main results.First, the similarity between Brazil`s and China`s export has increased until 2005 and after that has fallen. Second, the quality of Brazil`s exports is, on average, higher than China`s exports. The quality index has remained constant in the beginning and then increased substantially over years 2006 and 2007. The increase in the quality index was significant in some sectors, as food and beverage, rubber and plastic, wood products and furniture, pulp and paper, textile and apparel, and metals. Third, the variety of China`s exports exceeded Brazil`s exports all over the period.
Keywords: F14; 330; Export; Internationaler Wettbewerb; Internationale Wirtschaftsbeziehungen; Brasilien; China; USA